LEGAL CERTAINTY ON COMBINED PROSECUTION OF THE CRIMINAL ACTION OF CORRUPTION WITH THE CRIME OF MONEY LAUNDERING (World Bulletin of Management and Law, 2023)
This study focuses on combining the prosecution of corruption which becomes a predicate crime in money laundering by using the theory of legal responsibility and the theory of legal certainty to answer the main problem formulated regarding the combination of prosecution of criminal acts of corruption with criminal acts of money laundering according to applicable law currently and the legal certainty of combining the prosecution of criminal acts of corruption with criminal acts of money laundering. The method used in this study is normative juridical research with a statutory and conceptual approach. The data used are secondary data sourced from primary legal materials that are authoritative and binding, secondary legal materials sourced from library materials and tertiary legal materials sourced from materials that provide an explanation of primary and tertiary legal materials by using library study techniques to be analyzed and presented in an analytical descriptive.